(untitled) (SCRIPTA SCORE Scientific Medical Journal, 2022)
Background: Constipation is common and affects 15% of population worldwide. Constipation can decrease the quality of life of the patients and may be affected by many factors, including stress. Stress too, is general, especially in students, causing higher rates in suicidal tendency and impairments from various aspects. Today, in COVID-19 pandemic, stress is more common due to numerous causes. One of the causes is online studying in COVID-19 pandemic, which might trigger stress in students. Objectives: To determine the relationship between online study stress in COVID-19 pandemic with constipation in the year 2018 medical students of USU in 2021. Method: This study is an analytical observational study using a cross-sectional design. Samples in this study were 112-year 2018 medical students of USU who satisfied the inclusion criteria and gathered by using a consecutive sampling method. Primary data were acquired by using an online- shared questionnaire in the google form and submitted by the respondents. Then, univariate, and bivariate analyses were performed on the data using SPSS, with the latter using fisher’s exact test. Results: In this study, 78 students (69,6%) were stressed and 8 students (7,1%) were constipated. The analysis between the two variables using fisher’s exact test shown the p value about 0,431, which can be interpreted as no association found between online study stress in COVID-19 pandemic with constipation. Conclusion: Online study stress in COVID-19 pandemic is not associated with constipation. Keywords: Constipation, Pandemic, Online study, Stress